Disharmony of Sirri Marriage Registration Regulation on the Family Card (Analyzing The Ministry of Interior Affairs’ Regulation No. 9/2016) - Lathifah Munawaroh; Ahmad Munif; Ahmad Rofiq (Fiat Justisia: Jurnal Ilmu Hukum, 2023)
The Regulation of the Minister of Interior Affairs of the Republic of Indonesia No. 9 of 2016 concerning the Acceleration of Coverage of Birth Certificate Ownership, in article 4 numbers 2 and 3, allows birth certificate applicants who cannot meet the requirements in the form of a marriage certificate, to get a solution still recorded in the family card by attaching the statement of absolute responsibility, called SPTJM, truth as husband and wife with the editorial status written in the family card "unregistered marriage." A breakthrough that invites controversial experts. On the one hand, contrary to Marriage Law No. 1 of 1974, on the other hand, the government wants to guarantee the right of every citizen to be registered so that administration is orderly. Through a qualitative method with a normative juridical approach, this study shows that the registration of marriages on the marriage certificate and family card aligns with the concept of maqāṣid sharī'ah. This recording also aligns with the principles of sadd al-ḍarī'ah, qiyās, and maslahah mursalah. Meanwhile, the apparent disharmony between marriage registration regulations and population administration records is also in line with the provisions of Islamic law. However, the Population Administration Registration Regulations make registering Sirri marriages a database to be followed up with mass marriage isbāt. The last door to register and legalize the marriage contract.